2016
DOI: 10.1371/journal.pone.0154698
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal Exposure to a Diet High in Saturated Fat, Refined Sugar and Cholesterol Affects Behaviour, Growth, and Feed Intake in Weaned Piglets

Abstract: The increased consumption of diets high in saturated fats and refined sugars is a major public health concern in Western human societies. Recent studies suggest that perinatal exposure to dietary fat and/or sugar may affect behavioural development. We thus investigated the effects of perinatal exposure to a high-fat high-sugar diet (HFS) on behavioural development and production performance of piglets. Thirty-two non-obese sows and their piglets were allocated to 1 of 4 treatments in a 2 × 2 factorial design, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 69 publications
2
12
0
2
Order By: Relevance
“…The impact of a calorie-dense perinatal diet (high in saturated fat, refined sugar, and cholesterol) on the development of piglets was examined (Clouard, Gerrits, Kemp, Val-Laillet, & Bolhuis, 2016). Prenatal exposure resulted in decreased basal salivary cortisol levels, relative to controls.…”
Section: Substance Use and Effects Of Psychotropic Medicationmentioning
confidence: 99%
“…The impact of a calorie-dense perinatal diet (high in saturated fat, refined sugar, and cholesterol) on the development of piglets was examined (Clouard, Gerrits, Kemp, Val-Laillet, & Bolhuis, 2016). Prenatal exposure resulted in decreased basal salivary cortisol levels, relative to controls.…”
Section: Substance Use and Effects Of Psychotropic Medicationmentioning
confidence: 99%
“…A large body of evidence has also highlighted the impact of early‐life nutrition on behavioral and brain functions related to eating behavior, food pleasure, and motivation. Specific preferences and motivation to consume fats and sweets were increased in offspring of nonobese rat dams exposed to a high‐calorie diet during gestation and lactation (13, 14), and Clouard et al (17) showed programming effects of a maternal WD on social behavior and voluntary feed intake of piglets later in life.…”
mentioning
confidence: 99%
“…The findings of the current study suggest that early feeding experiences can have long-lasting effects on feed preferences, at least up to two weeks after the treatments were not reinforced anymore. Our findings are consistent with previous studies, who also reported differences in short-(during dietary treatment) and long-term feeding preferences (after end of dietary treatments) in piglets exposed to different diets early in life (Figueroa et al, 2013;Blavi et al, 2016;Clouard et al, 2016).…”
supporting
confidence: 93%
“…However, our data on haptoglobin concentrations and weaningstress-induced behaviour do not support this hypothesis. Thirdly, providing fibrous creep feed may affect the responsiveness of piglets to novelty via the microbiota-gut-brain axis, because dietary composition has been shown to affect anxiety, exploration, agonistic and activity levels in pigs at various stages of life (Haagensen et al, 2014;Clouard et al, 2016). Indeed, the gut microbiota of CF-and NF-piglets differed in composition from 2 weeks of age (Choudhury, Middelkoop et al, in preparation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation